The safety and efficacy of remimazolam tosylate for induction and maintenance of general anesthesia in pediatric patients undergoing elective surgery: Study protocol for a multicenter, randomized, single-blind, positive-controlled clinical trial - Fang, Yu-Bo; Wang, Cheng-Yu; Gao, Yu-Qing; Cai, Yu-Hang; Chen, Jia; Zhang, Xu-Lin; Dong, Le-Qi; Shang-Guan, Wang-Ning; Liu, Hua-Cheng (Frontiers in Pharmacology, 2023)
Introduction: Remimazolam is an ultra-short-acting benzodiazepine sedative agent commonly used in general anesthesia, procedural sedation, and intensive care unit (ICU) sedation. This study aimed to explore the efficacy and safety of remimazolam versus propofol for the induction and maintenance of general anesthesia in preschool-age children undergoing elective surgery. Methods and analysis: In this multicentre, randomized, single-blind, positive-controlled non-inferior clinical trial, one hundred ninety-two children aged 3-6 years will be randomly allocated as a 3:1 ratio into two groups: Group R with an intravenous dose of remimazolam 0.3mg/kg for the induction of anesthesia followed by a constant infusion rate of remimazolam 1-3mg/kg/h to maintain anesthesia, and Group P with an intravenous dose of propofol 2.5mg/kg for the induction of anesthesia followed by a constant infusion rate of propofol 4-12mg/kg/h to maintain anesthesia. The primary outcome will be the rate of the successful induction and maintenance of anesthesia. The secondary outcomes will include the time to LoC, awakening time, extubation time, post-anesthesia care unit (PACU) discharge time, usage of additional sedative drugs during the induction period, usage of remedial drugs in PACU, emergence delirium, pain in PACU, behavior scores at day 3 after surgery, parental and anesthesiologists satisfaction, and adverse events. Ethics and dissemination: This study has been approved by the ethics review boards at all participating hospitals. The Ethics Committee of the Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University (Reference No. LCKY 2020-380, November 13, 2020) is the central ethics committee. Trial registration number: ChiCTR2100053468 (November 22, 2021)